Controversy Spokesperson of G20 Indonesia: A Critical Discourse Analysis Study - Tesalonika Hasugian; Silvanus Alvin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Bloomberg Businessweek has published the news titled G-20 Role for 27-year-old Indonesia Singer Sparks Criticism. The news contains controversy about Maudy Ayunda's role as a spokesperson for G20 Indonesia. The research is interesting because the power of international news can dominate the political issues of national media, especially since the person who gets attacked is a female gender figure who is also a celebrity. This research used qualitative and descriptive methods. The source of research data is a Bloomberg article written by Yudith Ho and Rieka Rahadiana in 2022. Text analysis was used to analyze the data, with an emphasis on women's discourse from Roger Fowler. The results show the existence of discourse battles carried out by critics. Wasisto Raharjo and Irfan Wahyudi's thoughts became an opinion subject because the government did not choose Maudy Ayunda correctly as the international spokesperson. From this analysis, this research contains an element of controversy and a reasonable interpretation that the point of view of critics is different from the point of view of ordinary people